Quality of Life and Caregiver Burden Scale in Iranian Children on Continuous Ambulatory Peritoneal Dialysis - Hooman, Nakysa; Tatarpoor, Parvin; Ahmadi, Mohammad; Jahangiri, Fariba; Ghaffari, Leila; Mamiyanloo, Haideh; Abdolreza- Gharebagh, Zahra; Hakim-Shooshtar, Mitra; Sharifian, Mostafa; Mazaheri, Mojgan; Nickavar, Azar (Journal of Pediatric Nephrology, 2019)
Introduction: Chronic kidney diseases are associated with a poor quality of life in patients and their families. Previous studies have shown a three-fold higher rate of exhaustion in peritoneal dialysis compared to hemodialysis patients and their families. Here we studied the quality of life and caregiver’s burden of children receiving chronic ambulatory peritoneal dialysis (CAPD) in comparison with other chronic diseases among pediatric patients. Materials and Methods: This prospective case-control survey was conducted between 2013 and 2014 in Ali- Asghar Children’s Hospital. The inclusion criteria were age below 18 years and having a chronic disease diagnosed at least six months earlier. The parents of 13 children on peritoneal dialysis (cases) and 160 children with other chronic diseases(controls) were requested to complete the Pediatric Quality of Life Inventory (PedsQL™ 4.0™) appropriate to the patient’s age and the Caregiver Burden Scale (CBS). Independent t-test was applied to compare the variables between the two groups. P-values < 0.05 were considered significant. Results: Overall, 353 questionnaires were completed. The CAPD group had a higher mean (SD) score of quality of life in all domains, including somatic symptoms [67 (25.6) vs. 18.5(15.6)], emotional symptoms [71(17) vs. 20.5(15.1)], and social functioning [58(32) vs. 21.3(20)] (p-value<0.001). In addition, the case group had a lower mean (SD) score of caregiver’s burden [50(16.7) vs. 80 (13.5)] compared to the control group (P value<0.001). Conclusions: CAPD children and their parents had better a PedsQL™ 4.0™ score and a lower CBS compared to children with other chronic diseases. The most affected area of the quality of life was school functioning in the CAPD group and somatic symptoms in the control group. Keywords: Quality of life; Renal Dialysis; Adaptation; Psychological; Chronic Disease; Child.